2017
DOI: 10.1080/15685551.2017.1368116
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of pH sensitive crosslinked Linseed polysaccharides-co-acrylic acid/methacrylic acid hydrogels for controlled delivery of ketoprofen

Abstract: Some pH responsive polymeric matrix of Linseed (Linum usitatissimum), L. hydrogel (LSH) was prepared by free radical polymerization using potassium persulfate (KPS) as an initiator, N,N-methylene bisacrylamide (MBA) as a crosslinker, acrylic acid (AA) and methacrylic acid (MAA) as monomers; while ketoprofen was used as a model drug. Different formulations of LSH-co-AA and LSH-co-MAA were formulated by varying the concentration of crosslinker and monomers. Structures obtained were thoroughly characterized using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Swelling Studies. The swelling ratio (dynamic swelling) of copolymers was performed up to 72 h, and equilibrium swelling of copolymers was continued for 2-3 weeks until a constant weight was achieved in 100 mL buffer solutions of different pH, respectively [25,26]. Dynamic and equilibrium swelling was calculated from the following formulas:…”
Section: Synthesis Of Artemisia Vulgaris-aammentioning
confidence: 99%
See 2 more Smart Citations
“…Swelling Studies. The swelling ratio (dynamic swelling) of copolymers was performed up to 72 h, and equilibrium swelling of copolymers was continued for 2-3 weeks until a constant weight was achieved in 100 mL buffer solutions of different pH, respectively [25,26]. Dynamic and equilibrium swelling was calculated from the following formulas:…”
Section: Synthesis Of Artemisia Vulgaris-aammentioning
confidence: 99%
“…where W1 is the initial weight of dried disc of copolymer and W0 is the weight of the dried insoluble part of copolymer after extraction with water [24,26].…”
Section: Synthesis Of Artemisia Vulgaris-aammentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion co-efficient represent the quantity of the solvent that diffuses through a unit area of the gel in unit time through concentration gradient [31]. Following parameters depends on the partial mobility of the solvent, that can be determined by the following equation 4:…”
Section: Diffusion Co-efficientmentioning
confidence: 99%
“…The pH-dependent response of acrylic acid-based polymers were also investigated as controlled drug carrier systems. A polymeric matrix comprising Linseed (Linum usitatissimum), L. hydrogels (LSH) was prepared by free radical copolymerization rout between acrylic and methacrylic (MAA) acids using N, N -methylene bis-acrylamide (MBA) as a crosslinking agent, and investigated as drug carrier of ketoprofen by Shabir et al [32] It was found that swelling of the copolymer hydrogels was the greatest at pH 7.4. The extent of ketoprofen release was found to increase as the monomer content increased, and decreasewhen the MBA content decreased.…”
Section: Introductionmentioning
confidence: 99%